The effect of 2 different dual-task balance training methods on balance and gait in older adults: a randomized controlled trial - POLAT, MİNE GÜLDEN; OĞUZ, SEMRA (My University, 2022)
Objective The purpose of this study was to compare the effects of integrated and consecutive cognitive dual-task balance training in older adults on balance, fear of falling, and gait performance. Methods Fifty-eight participants (age >65 years) were randomly assigned to an integrated dual-task training group (IDTT) (n = 29) and consecutive dual-task training group (CDTT) (n = 29). Balance exercises and cognitive tasks were performed simultaneously by the IDTT group and consecutively by the CDTT group for 8 weeks. Balance was assessed using the Berg Balance Scale as a primary outcome measure and the Timed \"Up & Go\" Test (TUG) (standard-cognitive), fear of falling was assessed using the Tinetti Falls Efficacy Scale, and gait speed was assessed using the 10-Meter Walk Test (10MWT) (under single-task and dual-task conditions). All tests were performed before and after the training. Results There was no difference in group-time interaction in the Berg Balance Scale, TUG-standard, 10MWT-single task, and 10MWT-dual task tests. Group-time interaction was different in the TUG-cognitive and Tinetti Falls Efficacy Scale scores. Also, the effect of time was significantly different in all scales except for the 10MWT-single task in both groups. Conclusion At the end of the 8-week training period, the impact of integrated and consecutive dual-task balance training on balance and gait performance in older adults was not statistically significantly different. This study suggests that consecutive dual-task balance training can be used as an alternative method to increase balance performance and gait speed in older adults who cannot perform integrated dual-task activities. Impact There were no significant differences between the effects of the 2 dual-task training methods on balance and gait speed, suggesting that the consecutive dual-task balance training method can be used to improve the balance and gait of older adults. CDTT can be performed safely and considered as an alternative method for use in many rehabilitation training programs with older adults who cannot perform simultaneous activities.
Keywords: ORTOPEDİ; Klinik Tıp; Klinik Tıp (MED); REHABİLİTASYON; ORTHOPEDICS; CLINICAL MEDICINE; Clinical Medicine (MED); REHABILITATION; Dual-Task; Exercise; Balance; Gait; Older Adults; WALKING SPEED; PARKINSONS-DISEASE; GENDER-DIFFERENCES; FALLS EFFICACY; SINGLE-TASK; PERFORMANCE; FEAR; MOTOR; RISK; INTERFERENCE; Dual-Task; Exercise; Balance; Gait; Older Adults